(untitled) (International Journal of Engineering and Computer Science, 2017)
Estimating human age automatically via facial Image analysis has lots of potential real-world application, such as human computer interaction and multimedia communication. It is rapidly entering in all the sectors and aspects of our life. In this work the identification of younger image and older image are Focused on the methods using MATLAB. First we extract certain features from the input Face images, later using different method like thresholding, segmentation, edge detection and thus we get related databases. Comparing several trained databases, we get a specific range for younger images and older images. From the proposed range we can identify the young and old face. Thus this paper analysis the younger and older images with a very high accuracy successfully using image processing.